Food hygiene practices of mothers and level of contamination in child's food in Nepal: a formative research - Om Prasad Gautam; Val Curtis (2013)
Preventable and treatable food-borne diseases are a major cause of illness globally. Inadequate food hygiene is likely to cause a substantial proportion of foodborne infections including diarrhoea among infants and young children. Although proper food hygiene practices may prevent disease, there is little evidence to support this premise. Very few intervention studies have been carried out and there has been little effort to undertake food hygiene interventions for the reduction of childhood diarrhoea and malnutrition. A simple and replicable food hygiene intervention, which can be implemented by the WASH, health and nutrition sectors at scale has yet to be designed and tested. The formative research was conducted in a rural hill setting in Nepal during April-June 2012, examining mothers’ food hygiene practices and their environmental and psychological determinants, the level of microbes in the child’s food, and critical and behavioral control points. Formative research helped to prioritize five key food hygiene behaviours for the design of an intervention in the next phase of the PhD research.